Preliminary clinical testing to inform development of the Critical Care Pain Observation Tool for Families (CPOT-Fam) - Anmol Shahid; Bonnie G. Sept; Victoria S. Owen; Corson Johnstone; Rameiya Paramalingam; Stephana J. Moss; Rebecca Brundin-Mather; Karla D. Krewulak; Andrea Soo; Jeanna Parsons-Leigh; Céline Gélinas; Kirsten M. Fiest; et al. (Canadian Journal of Pain, 2023)
ABSTRACTIntroduction Many patients in the intensive care unit (ICU) cannot communicate. For these patients, family caregivers (family members/close friends) could assist in pain assessment. We previously adapted the Critical Care Pain Observation Tool (CPOT) for family caregiver use (CPOT-Fam). In this study, we conducted preliminary clinical evaluation of the CPOT-Fam to inform further tool development.Methods For preliminary testing, we collected (1) pain assessments of patients in the ICU from family caregivers (CPOT-Fam) and nurses (CPOT) and determined the degree of agreement (kappa coefficient, κ) and (2) collected openended feedback on the CPOT-Fam from family caregivers. For refinement, we used preliminary testing data to refine the CPOT-Fam with a multidisciplinary working group.Results We assessed agreement between family caregiver and nurse pain scores for 29 patients. Binary agreement (κ) between CPOT-Fam and CPOT item scores (scores ≥2 considered indicative of significant pain) was fair, κ = 0.43 (95% confidence interval [CI] 0.18–0.69). Agreement was highest for the CPOT-Fam items ventilator compliance/vocalization (weighted κ = 0.48, 95% CI 0.15–0.80) and lowest for muscle tension (weighted κ = 0.10, 95% [CI] −0.17 to 0.20). Most participants (n = 19; 69.0%) reported a very positive experience using the CPOT-Fam, describing it as “good” and “easy-to-use/clear/straightforward.” We iteratively refined the CPOT-Fam over five cycles using the data collected until no further revisions were suggested.Conclusion Our preliminary clinical testing suggests that family involvement in pain assessment in the ICU is well perceived. The CPOT-Fam has been further refined and is now ready for clinical pilot testing to determine its feasibility and acceptability.